Analisis Cyber Awareness terhadap Keamanan Data Pribadi dari Serangan Siber menggunakan Metode AHP - Ayu Astridefi; Rudy A.G. Gultom; Yudistira Dwi Wardhana Asnar (Journal on Education, 2024)
With the increasing number of cyber-attacks and data breaches, individuals and organizations must be proactive in protecting their sensitive personal data and information. Personal data security is a critical concern as individuals and organizations face increasing threats from cyber-attacks. One effective way to evaluate and improve personal data security is through the use of the Analytic Hierarchy Process (AHP) method. This paper presents a study that utilizes AHP to analyze the level of cyber awareness among individuals and the effect it has on the security of their personal data. A survey was conducted to gather data from a sample group of individuals, and the results were analyzed using AHP. The results of the study showed that there is a positive correlation between an individual's level of cyber awareness and the security of their personal data. The study also identified areas where individuals can improve their cyber awareness and, in turn, increase the security of their personal data. This research contributes to the field of personal data security by providing a practical and effective method for evaluating and improving an individual's cyber awareness.